RETRACTED: Upaya Hukum Cessionaris Terhadap Hak Tagih Atas Jaminan Hak Tanggungan Berdasarkan Pengalihan Hutang (Cessie) - Diana Fitriana; Abdul Wahid (Jurnal Hukum Sasana, 2021)
This article has been retracted at the request of publisher. Reason: This article is virtually identical to the previously published article "Upaya Hukum Cessionaris Terhadap Hak Tagih Atas Jaminan Hak Tanggungan Berdasarkan Pengalihan Hutang (Cessie), Lex jurnalica, Volume 18 No. 3 (2021), 246-257 authored by Diana Fitriana, Abdul Wahid, Urip Giyono.